PENGARUH EDUKASI MENGGUNAKAN BUKU INFORMASI KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG KESEHATAN REPRODUKSI DI SMP N 1 SIBOLGA TAHUN 2020 - Nasution, Herlina (Jurnal Inovasi Kesehatan Masyarakat, 2021)
Teenagers need to have knowledge about reproduction health. Not only take care of the organs’ health and function but the right information can make them avoid doing unexpected cases. The purpose of this research was to analyze the influence of education by using the health information books on the knowledge and attitude of the student in SMPN I Sibolga in 2020. The design of this research was one group pretest and posttest design.It was performed through lecture method and had them read the health information books during 2 days.The sample of this research was third year students with 70 members. They were taken by simple random sampling method.The data were got based their answers on the questionnaire of knowledge and attitude. The implemented assessement was Paired Simple T-Test. The result of this research showed that there was increase in their average score either knowledge and attitude after education. For knowledge weat up from 62,86 to 89,20 and 104,24 to 142,44 for attitude. So we could see they had 26,34 point increase in knowledge and 38,2 in attitude. The conclusion is education by using health information books gave a positive influence on the teenagers’ knowledge and attitude concerning with reproduction health. The p-value was gotten 0,000 < 0,05.Health service activities at schools especially about reproduction health of teenager need to do more and more in Sibolga.